OUR EXPERIENCE OF IMMUNOHISTOCHEMICAL ASSAY IN BREAST CANCER - S.R. RASULOV; SH.A. VASIKHOV (Avicenna Tajik State Medical University, 2020)
Objective: Analysis of the first experience of immunohistochemical (IHC) diagnostics of breast cancer (BC) in the Republic of Tajikistan for 2018- 2020. Methods: The results of the IHC study of tumor samples obtained by trephine biopsy in 142 patients and the surgical material after radical surgery in 110 patients have been studied. DAKO (Denmark) standard sets used for IHC assay. The staining carried out by manual methodology of the standard protocol provided by the company. The expression of ER and PR, HER2/neu and Ki-67 was determined. Receptive body expression of the ER and PR was evaluated by a point system, by the color intensity and the proportion of stained cells. The degree of HER2/neu expression was determined based on the staining of tumor cell membranes. To determine the threshold value of Ki-67 and subtypes of BC, we used the recommendations of the panel of experts of the St. Gallen Conference on Breast Cancer, proposed in 2013. Results: ER- and PR-positive tumors were found in 54.8% of patients. Negative expression of ER and PR was observed in 38.9% of cases. HER2/neu negative tumor status was found in 68.4%, HER2/neu positive - in 28.8% of cases. Low proliferative activity of Ki-67 was observed in 35.3% of patients, and high proliferative activity - in 64.7% of women. Three times negative BC was found in 23% of patients. Conclusion: High proliferation of steroid hormone receptors, the low proliferation of Ki-67 and absence of HER2/neu are considered favorable prognostic factors. Overexpression of HER2/neu is an unfavorable prognostic sign. High proliferation of Ki-67 is a direct indication for prescribing chemotherapeutic treatment. If technical capabilities are available, the IHC method should be developed in clinics where diagnostic and treatment of BC are conducted.